Discrete-time sliding mode protocols for leader-following consensus of discrete multi-agent system with switching graph topology. (January 2020) - Patel, Keyurkumar; Mehta, Axaykumar
Abstract: In this paper, discrete-time sliding mode protocols for consensus of a leader following discrete multi-agent system having switching topologies are proposed. The discrete multi-agent system is described with a fixed, undirected switching graph topology as a global system having one leader and other as follower agents. Sliding surface for global consensus of agents for switching graph topology is defined and discrete-time sliding mode protocols using enhanced Gao's and Power rate reaching laws are derived. Under the influence of switching topology, the graph topology switches in a different no. of step intervals and ensure that consensus protocols asymptotically synchronize follower agents with leader agent. The condition for global stability in both cases is also derived using the Lyapunov function. Further, the algorithms are implemented on the multi-agent system comprise of multiple 2-DOF (Degree of Freedom) helicopter systems where the pitch angle and its velocity & yaw angle and its velocity are synchronized with the leader. It is inferred from simulation results that the consensus using Power rate reaching law give better performance compared with consensus using Gao's reaching law. Finally, the robustness property of both the algorithms is checked by applying the matched disturbances in follower agents.